Perancangan Template Promosi di Instagram dengan Menggunakan Aplikasi Powerpoint Untuk Untuk Pemasaran Pengusaha Kuliner di Kota Malang - Amar Ma’ruf Stya Bakti; Sultan Arif Rahmadianto (G-Tech: Jurnal Teknologi Terapan, 2023)
In this digital era, food and beverage businesses leverage it to market their products. This includes activities such as brand development, social media promotion, hiring brand ambassadors, and more. Among the various alternatives for marketing their products, one simple and straightforward promotional method is utilizing Instagram feed layouts designed using PowerPoint software. The reason for choosing this software is its widespread availability and ease of use, as most people have it on their laptops or desktop computers (PCs). The method employed is the qualitative ADDIE model, which consists of several stages, including Analysis, Design, Development, Implementation, and Evaluation. This method offers the advantage of a structured process and flexibility in applying it to creative content and projects. The outcome is a promotional media design template used by small and medium-sized food and beverage businesses to sell their products on the Instagram platform